2010
DOI: 10.1593/neo.10916
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil Factor 3 Is Oncogenic and Mediates Anti-Estrogen Resistance in Human Mammary Carcinoma

Abstract: We report herein that trefoil factor 3 (TFF3) is oncogenic and mediates anti-estrogen resistance in human mammary carcinoma. Forced expression of TFF3 in mammary carcinoma cells increased cell proliferation and survival, enhanced anchorage-independent growth, and promoted migration and invasion. Moreover, forced expression of TFF3 increased tumor size in xenograft models. Conversely, depletion of endogenous TFF3 with small interfering RNA (siRNA) decreased the oncogenicity and invasiveness of mammary carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
114
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(132 citation statements)
references
References 66 publications
16
114
2
Order By: Relevance
“…We have previously shown that TFF3 activates cell survival signaling pathways which contribute to anti-estrogen resistance in mammary carcinoma [16]. TFF3-enhanced cell survival and tamoxifen resistance have both been suggested to be dependent on BCL-2 [16]. Consistently in this study, we identified BCL-2 as an important downstream mediator of cell survival and doxorubicin resistance in HCC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We have previously shown that TFF3 activates cell survival signaling pathways which contribute to anti-estrogen resistance in mammary carcinoma [16]. TFF3-enhanced cell survival and tamoxifen resistance have both been suggested to be dependent on BCL-2 [16]. Consistently in this study, we identified BCL-2 as an important downstream mediator of cell survival and doxorubicin resistance in HCC.…”
Section: Discussionsupporting
confidence: 89%
“…Real-time quantitative PCR (qPCR) was also performed to analyse mRNA expression levels [16]. Primer used for RT-PCR and qPCR are as previously described [81].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, detecting or preventing cervical cancers with progressions in early is critical, which could help to prolong patient survival. As we know TFF3 is a soluble peptide containing trefoil domain and C-terminal dimerization domain which is not only a novel prognostic marker but also a therapeutic target in various cancers, such as mammary carcinoma, gastric cancer and prostate carcinoma [58]. Upregulation of TFF3 after rectal cancer chemo-radiotherapy is an adverse prognostic factor [9].…”
Section: Introductionmentioning
confidence: 99%
“…TFF3, behaved as an oncogene, promotes proliferation and invasion, improves survival, and increases oncogenicity in cancer cells, such as mammary carcinoma, gastric cancer and prostate carcinoma [5, 11]. TFF3 promoted epithelial tumorigenesis by inducing aberrant proliferation and inhibiting apoptosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…The trefoil factor family is characterized by a 40 amino acid motif and interestingly another member of this family, TFF3, is found in the feature list of the combined model (Supplemental Table 1). TFF3 expression is positively correlated with the status of the estrogen receptor in adenocarcinoma [25] and TFF3 is furthermore associated with breast cancer invasion and metastasis [26], as well as treatment resistance [27].…”
Section: Most Important Featuresmentioning
confidence: 99%